2012
DOI: 10.1073/pnas.1201608109
|View full text |Cite
|
Sign up to set email alerts
|

Bax regulates primary necrosis through mitochondrial dynamics

Abstract: The defining event in apoptosis is mitochondrial outer membrane permeabilization (MOMP), allowing apoptogen release. In contrast, the triggering event in primary necrosis is early opening of the inner membrane mitochondrial permeability transition pore (mPTP), precipitating mitochondrial dysfunction and cessation of ATP synthesis. Bcl-2 proteins Bax and Bak are the principal activators of MOMP and apoptosis. Unexpectedly, we find that deletion of Bax and Bak dramatically reduces necrotic injury during myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
226
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(241 citation statements)
references
References 38 publications
14
226
1
Order By: Relevance
“…Recent genetic studies revealed that deletion of Bax/ Bak inhibits mPTP opening and necrotic cell death induced by Ca 2+ overload or ROS, suggesting the ability of Bax/Bak to facilitate mPTP-induced cell death. 113,114 Thus the aforementioned mitoHK-II-mediated inhibition of Bax binding to mitochondria could contribute to the anti-mPTP effect of mitoHK-II. Further studies will be required to delineate the interaction of these molecules to determine the mechanism by which HK-II prevents mPTP opening.…”
Section: Pro-survival Effect Of Hk-iimentioning
confidence: 99%
“…Recent genetic studies revealed that deletion of Bax/ Bak inhibits mPTP opening and necrotic cell death induced by Ca 2+ overload or ROS, suggesting the ability of Bax/Bak to facilitate mPTP-induced cell death. 113,114 Thus the aforementioned mitoHK-II-mediated inhibition of Bax binding to mitochondria could contribute to the anti-mPTP effect of mitoHK-II. Further studies will be required to delineate the interaction of these molecules to determine the mechanism by which HK-II prevents mPTP opening.…”
Section: Pro-survival Effect Of Hk-iimentioning
confidence: 99%
“…Although MOMP and mPTP appear to be distinct pathways, a cross-talk has been reported between them. Mice deficient in Bax/Bak render cells resistant to mPTP opening and necrosis (451). Superoxide-induced mitochondrial Cyt-c release in HepG2 cells depends on VDAC, and blockers of VDAC inhibited the release (259).…”
Section: B Intrinsic Pathways Of Cell Death and Regulation By Rosmentioning
confidence: 99%
“…This may be significant with respect to the variability in cardioprotection provided by cyclosporine A because the fused mitochondrial state sensitizes to mPTP opening. 14 Second, although experiments using mice lacking cyclophilin D 8,9 and cyclosporine A 3 implicate mPTP opening in reperfusion injury, might other death processes provide redundancy when mPTP opening is inhibited? In fact, genetic and pharmacological data suggest that necroptosis may contribute to infarct size in heart and kidney following ischemia/reperfusion injury.…”
Section: +mentioning
confidence: 99%